Od egzotyzacji do inspiracji. Mazurscy staroobrzędowcy w polskich narracjach fiction i non-fiction w XX i XXI wieku - Szydłowska, Joanna (Acta Neophilologica, 2020)
This paper analyzes the presence of the Old Believers in Polish media and literary discourses of the 21st century. Special focus is placed on the exoticization pro-cedures of otherness with respect to the Old Believers’ communities. Instrumentaliza-tion mechanisms in the following modules are described: national and anthropological, autobiographical, popcultural and eschatological.